Inhibition of intracellular growth of Listeria monocytogenes by antibiotics. - Michelet, C (1994)
We studied the activities of 15 antibiotics on the intracellular growth of Listeria monocytogenes in a HeLa cell line. After 24 h of contact with the infected cells, the antibiotics most effective against the intracellular growth of the 10 strains tested were amoxicillin, temafloxacin, and sparfloxacin, which nevertheless failed to totally eliminate the intracellular bacteria. Rifampin and co-trimoxazole had variable effects, depending on the isolates studied. The most active combinations were amoxicillin-sparfloxacin, co-trimoxazole-gentamicin, and sparfloxacin-co-trimoxazole. The results suggest the value of using a cell culture technique to study the activities of antibiotics against certain bacteria with intracellular sites of multiplication.